A new genus and species of Nothomorphina Cobos, 1955 from northwestern South Africa (Coleoptera: Buprestidae: Polycestinae) - Bellamy, C. L. (Zootaxa, 2005)
A new genus and species, Richtersveldia insperata Bellamy, gen. & sp. nov., is described from the Northern Cape Province, South Africa. The new genus is placed in the subtribe Nothomorphina Cobos, 1955 and a key to separate the four genera in that subtribe is given. The new species is illustrated with one color plate showing different aspects of habitus and close-ups of head, antenna and aedeagus.